Arabidopsis CRL4 Complexes: Surveying Chromatin States and Gene Expression - Fonseca, Sandra; Rubio, Vicente (Frontiers in Plant Science, 2019)
CRL4 complexes contain a CUL4 scaffold protein, associated to RBX1 and to DDB1 proteins and have traditionally been associated to protein degradation events. Through DDB1, these complexes can associate with numerous DCAF proteins, which directly interact with specific targets promoting their ubiquitination and subsequent degradation by the proteasome. A characteristic feature of the majority of DCAF proteins that associate with DDB1 is the presence of the DWD motif. DWD-containing proteins sum up to 85 in the plant model species Arabidopsis. In the last decade, numerous Arabidopsis DWD proteins have been studied and their molecular functions uncovered. Independently of whether their association with CRL4 has been confirmed or not, DWD proteins are often found as components of additional multimeric protein complexes that play key roles in essential nuclear events. The significance of their complex partnership is still unexplored for most of DWD proteins. Here we summarize recent findings involving both confirmed and putative CRL4-associated DCAF proteins in regulating nuclei architecture remodelling, DNA damage repair, histone post-translational modification, mRNA processing and export, and ribosome biogenesis, that definitely have an impact in gene expression and de novo protein synthesis. We hypothesized that, by maintaining accurate levels of regulatory proteins through targeted degradation and transcriptional control, CRL4 complexes help to surveil nuclear processes essential for plant development and survival.